PEMBAHARUAN PENDIDIKAN ISLAM HARUN NASUTION (Kajian Filsafat Pendidikan) - Kasmiati Kasmiati (Scolae: Journal of Pedagogy, 2019)
his article shows the renewal of Islamic education by Harun Nasution in terms of educational philosophy. Aaronstrongly believed that the superiority of human reason. Harun then asserted that reason can understand the purpose ofrevelation, so that reason and revelation can be in line and in line in creating civilization. According to Harun that alQur'an and hadith both give a high position to reason and seek knowledge. According to him that this high appreciationof reason gives rise to a liberal theological style in Islam, in addition to the revelations coming down to help the humanmind in knowing things that lie beyond the reach of human reason. This has earned ijtihad according to him is the thirdsource in Islam, in addition to al-Qur'an and hadith. Ijtihad in various fields has given birth to the face of Islam in manyaspects, such as: theology, worship, morals, mysticism, philosophy, history and culture. Knowledge that is only one ortwo aspects or one aspect will only lead to incomplete understanding, misunderstanding, narrow and rigid.